Impact of age on liver damage, inflammation, and molecular signaling pathways in response to femoral fracture and hemorrhage - Meng, Fanshuai; Zhou, Yuzhuo; Wagner, Alessa; Bülow, Jasmin Maria; Köhler, Kernt; Neunaber, Claudia; Bundkirchen, Katrin; Relja, Borna (Frontiers in Immunology, 2023)
Background: Trauma causes disability and mortality globally, leading to fractures and hemorrhagic shock. This can trigger an irregular inflammatory response that damages remote organs, including liver. Aging increases the susceptibility to dysregulated immune responses following trauma, raising the risk of organ damage, infections, and higher morbidity and mortality in elderly patients. This study investigates how aging affects liver inflammation and damage post-trauma. Methods: 24 male C57BL/6J mice were randomly divided into four groups. Twelve young (17-26 weeks) and 12 aged (64-72 weeks) mice were included. Mice further underwent either hemorrhagic shock (trauma/hemorrhage, TH), and femoral fracture (osteotomy) with external fixation (Fx) (THFx, n=6) or sham procedures (n=6). After 24h, mice were sacrificed. Liver injury and apoptosis were evaluated using hematoxylin-eosin staining and activated caspase-3 immunostaining. CXCL1 and infiltrating polymorphonuclear leukocytes (PMNL) in the liver were assessed by immunostaining, and concentrations of CXCL1, TNF, IL-1β, and IL-10 in the liver tissue were determined by ELISA. Gene expression of Tnf, Cxcl1, Il-1β, and Cxcl2 in the liver tissue was determined by qRT-PCR. Finally, western blot was used to determine protein expression levels of IκBα, Akt, and their phosphorylated forms. Results: THFx caused liver damage and increased presence of active caspase-3-positive cells compared to the corresponding sham group. THFx aged group had more severe liver injury than the young group. CXCL1 and PMNL levels were significantly higher in both aged groups, and THFx caused a greater increase in CXCL and PMNL levels in aged compared to the young group. Pro-inflammatory TNF and IL-1β levels were elevated in aged groups, further intensified by THFx. Anti-inflammatory IL-10 levels were lower in aged groups. Tnf and Cxcl1 gene expression was enhanced in the aged sham group. Phosphorylation ratio of IκBα was significantly increased in the aged sham group versus young sham group. THFx-induced IκBα phosphorylation in the young group was significantly reduced in the aged THFx group. Akt phosphorylation was significantly reduced in the THFx aged group compared to the THFx young group. Conclusion: The findings indicate that aging may lead to increased vulnerability to liver injury and inflammation following trauma due to dysregulated immune responses.